2011
DOI: 10.4103/0970-9290.90323
|View full text |Cite
|
Sign up to set email alerts
|

Allele, genotype, and composite genotype effects of IL-1A +4845 and IL-1B +3954 polymorphisms for chronic periodontitis in an Indian population

Abstract: The distribution of the IL-1 positive composite genotype is in concordance with the frequencies reported in the Caucasians. Association was not found for the effect of allele, genotype, composite genotype, and haplotypes of IL-1A+4845 and IL-1B+3954 polymorphisms with periodontitis. Its utility as a risk marker in this population was not borne out by the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, contradictory results were obtained in a recently published data 28 where they have found that for IL-1β +3954 CC genotype was the more frequently genotype identified in cases than in controls.…”
Section: Resultsmentioning
confidence: 81%
“…However, contradictory results were obtained in a recently published data 28 where they have found that for IL-1β +3954 CC genotype was the more frequently genotype identified in cases than in controls.…”
Section: Resultsmentioning
confidence: 81%
“…The studies used various genotyping methods, including polymerase chain reaction-restriction fragment length polymorphism, polymerase chain reaction with sequence-specific primers and TaqMan analysis. Five studies were not in agreement with the Hardy-Weinberg equilibrium of the genotype distribution in the controls [ 11 , 12 , 20 , 32 , 36 ]. Seven studies enrolled Indian subjects [ 25 , 27 , 30 – 32 , 35 , 36 ], and eight enrolled Chinese subjects [ 11 , 12 , 19 , 20 , 22 , 24 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cultured human umbilical vein endothelial cells, IL1β activated VCAM-1 gene expression ( 29 ). Several previous studies have demonstrated strong associations between the high frequency of genetic polymorphism in IL1β and the development of severe chronic periodontitis ( 30 – 32 ). Gursoy et al ( 33 )revealed that IL1β was the only biomarker associated with periodontitis among the salivary cytokines and enzymes tested.…”
Section: Discussionmentioning
confidence: 97%